Analysis of the knowledge, attitudes and preventive practices of the female peruvian population on HIV-SIDA according to demographic and family health survey (ENDES) 2013- 2017 - Pasco-Salcedo, Cecilia Verónica (2020)
Objetive. To analyze the knowledge, attitudes and preventive practices of the Peruvian female population on HIV-AIDS according to Demographic and Family Health Survey (ENDES) 2013-2017. Material and methods: The results of the National Demographic Survey on Health (ENDES) continued 2013-2017 were used. The dependent variables were knowledge, attitudes and preventive practices against the disease. Results: The departments with the highest knowledge were for 2013: Tumbes (26.7%) and Ucayali (26.7%), Tacna (23.5%), Junín (19.1%), Lima (19.0 %) and Lambayeque (18.7%), and by 2017, higher knowledge was found in: Callao (16.8%), Tacna (16,4%), Tumbes (16.0%) and Lambayeque (16.0%), Lima (15,6%) and Ica (13.1%). The highest percentage of high knowledge (> 80%) of the age group were 30-34 years for 2013 and 2017, and 40-44 years for 2014, 2015, 2016. The type of place of residence was the Urban; and Rural in 2014. The natural region was Metropolitan Lima. The usual place of residence was the Capital. The educational level was the postgraduate level, and Higher-University level for 2017. The socioeconomic stratum was the Very rich. The question with the highest percentage of correctness of knowledge answered most frequently was the number 1º, Do you know where the HIV test is performed? The question with the lowest percentage of correct attitude was the number 5º If a doctor has infection due to HIV, should he be allowed to continue his work in the health facility? The question with the lowest percentage of practice success was number 1º Used Condom use in your last sexual relationship?. Conclusions: The knowledge of the Peruvian female population on HIV-AIDS according to Demographic and Family Health Survey (ENDES) 2013-2017 is the most common knowledge, the appropriate attitudes are located in the 63% percentile, and the practices Global preventives are incorrect.